The influence of temperature and humidity on swelling and surfactant migration in acrylic emulsion paint films. (3rd July 2016) - Ziraldo, Ian; Watts, Kristen; Luk, Arnold; Lagalante, Anthony F.; Wolbers, Richard C.
Abstract : It has often been observed anecdotally and implied through experimentation that acrylic emulsion paintings accumulate and entrain soils over time due to the inherent mechanical softness in artist's acrylic paint films, through the presence of hydrophilic film components, and by virtue of the ubiquitous presence of surfactant moieties on these film surfaces once they dry. In the present study, it has been this last effect that we have sought to describe more fully in terms of surfactant responsiveness to both temperature and relative humidity (RH). Surfactant hydration and dehydration under varying temperature and RH conditions affects the ultimate partitioning of the surfactant at the paint–air interface, as well as the inherent size, aggregation tendencies, and solubility of surfactant in the bulk paint materials which contain components that are highly responsive to changes in temperature and RH (e.g. polyacrylic or polymaleic anhydride-type dispersal materials). In this work, analytical techniques including three-dimensional microscopy and quartz crystal microbalance with dissipation were used to add to and reinforce current understanding of the physical and mechanical changes to acrylic paint films with temperature and RH. The migration of surfactant at the film surface was studied using desorption electrospray ionization-mass spectrometry and attenuated total reflectance Fourier transform infrared microscopy.